Parallel lossless image compression using Huffman and arithmetic coding - Howard, Paul G.; Vitter, Jeffrey Scott (Information processing letters, 1996)
We show that high-resolution images can be encoded and decoded efficiently in parallel. We present an algorithm based on the hierarchical MLP method, used either with Huffman coding or with a new variant of arithmetic coding called quasi-arithmetic coding. The coding step can be parallelized, even though the codes for different pixels are of different lengths; parallelization of the prediction and error modeling components is straightforward.